Support workers and the health professions in international perspective the invisible providers of health care. (Sociology of health professions., 2020)
This original collection analyses the global experience of health care support workers (HSWs) and examines their interface with the health professions, regulatory practice risks, employment challenges and the dilemmas of an ageing population. Crucial future policy recommendations are also made for a world becoming increasingly dependent on HSWs.